2008
DOI: 10.1111/j.1095-8649.2008.01957.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of Southern Ocean skates (Bathyraja) reveals a new species of Antarctic skate

Abstract: Two regions of mtDNA, cytochrome b and cytochrome c oxidase subunit 1, were sequenced in nine species of Bathyraja from the Southern Ocean and New Zealand. Based on sequence divergence, the species that has been referred to as Bathyraja eatonii from the Antarctic continental shelf and slope is a species distinct from B. eatonii from the Kerguelen Plateau (the type locality) and is a new and undescribed species Bathyraja sp. (cf. eatonii). There was no sequence divergence among samples of Bathyraja sp. (dwarf) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 38 publications
(51 reference statements)
1
43
0
1
Order By: Relevance
“…Similar results were found in studies on Isopoda (e.g. Held and Wägele 2005, Raupach and Wägele 2006, Raupach et al 2007, Brökeland and Raupach 2008, Bivalvia ), Octopoda (Allcock et al 2004, Strugnell et al 2008, Pycnogonida (Mahon et al 2008), Crinoidea (Wilson et al 2007) and benthic fi sh (Smith et al 2008). Some reasons for the possible circum-Antarctic distribution of some breeding taxa is the dispersal via the Antarctic Circumpolar Current (ACC hypothesis) or extinction of a high proportion of taxa with pelagic development during vicariant events (extinction hypothesis) or the speciation enhanced in taxa with nonpelagic development in refuges during glacial maxima over the Antarctic Continental Shelf in the Pliocene/ Pleistocene (ACS hypothesis) (Pearse et al 2009).…”
Section: Does Circum-antarctic Distribution Occur Amongst Species Of supporting
confidence: 75%
“…Similar results were found in studies on Isopoda (e.g. Held and Wägele 2005, Raupach and Wägele 2006, Raupach et al 2007, Brökeland and Raupach 2008, Bivalvia ), Octopoda (Allcock et al 2004, Strugnell et al 2008, Pycnogonida (Mahon et al 2008), Crinoidea (Wilson et al 2007) and benthic fi sh (Smith et al 2008). Some reasons for the possible circum-Antarctic distribution of some breeding taxa is the dispersal via the Antarctic Circumpolar Current (ACC hypothesis) or extinction of a high proportion of taxa with pelagic development during vicariant events (extinction hypothesis) or the speciation enhanced in taxa with nonpelagic development in refuges during glacial maxima over the Antarctic Continental Shelf in the Pliocene/ Pleistocene (ACS hypothesis) (Pearse et al 2009).…”
Section: Does Circum-antarctic Distribution Occur Amongst Species Of supporting
confidence: 75%
“…The cytochrome b gene was chosen as it can successfully distinguish skate species (Smith et al 2008). Sequences were aligned alongside those of outgroups Mitsukurina owstoni (GenBank accession EU528659) and Scyliorhinus canicula (GenBank accession Y16067).…”
Section: (D) Phylogenetics Of Rajiformesmentioning
confidence: 99%
“…However, in each case, sequences fell into two distinct groups separated by 1.2% and 1.1% sequence divergence, respectively. Prior barcoding studies on elasmobranchs have shown that COI divergences are lower than in most other chordates (Spies et al 2006;Smith et al 2008;Ward et al 2008), perhaps reflecting their lower rates of mtDNA evolution (Martin and Palumbi 1993;Johns and Avise 1998).…”
Section: Elasmobranchsmentioning
confidence: 99%
“…A comprehensive database of COI sequences, linked to authoritatively identified voucher specimens for all fishes, would represent a major advance for fisheries science (Becker et al 2011;Costa and Carvalho 2011;Ward et al 2009). Aside from providing identifications for adults, this reference library would allow the identification of all life stages (Côté et al 2013;Smith et al 2005).…”
Section: Introductionmentioning
confidence: 99%